2015
DOI: 10.1002/ijc.29507
|View full text |Cite
|
Sign up to set email alerts
|

Niemann-Pick type C2 protein regulates liver cancer progressionviamodulating ERK1/2 pathway: Clinicopathological correlations and therapeutical implications

Abstract: Primary hepatocellular carcinoma (HCC) is the fifth most common malignancy worldwide and the third leading cause of cancer-related death. It is important to identify new targets for early diagnosis and treatment of HCC. Niemann-Pick type C2 (NPC2) plays an important role in the regulation of intracellular cholesterol homeostasis via direct binding with free cholesterol. However, little is known about the significance of NPC2 in HCC tumorigenesis. In this study, we showed that NPC2 is abundantly expressed in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…As for invasion assay, we found that knockdown of survivin protein inhibited the invasive abilities of BGC823 cells into Matrigel compared with control. Consistent with our findings, recent articles also reported the silencing of survivin also affected the capacity of migration and invasion of a variety of cancers, such as breast cancer [13] and liver cancer [18].…”
Section: Discussionsupporting
confidence: 92%
“…As for invasion assay, we found that knockdown of survivin protein inhibited the invasive abilities of BGC823 cells into Matrigel compared with control. Consistent with our findings, recent articles also reported the silencing of survivin also affected the capacity of migration and invasion of a variety of cancers, such as breast cancer [13] and liver cancer [18].…”
Section: Discussionsupporting
confidence: 92%
“…Hep3B (purchased from BCRC, No. 60434) and Huh-7 [55] cells were infected with lentivirus in medium containing polybrene (8 ”g/mL) for the generation of stable cell lines. After 24 h of infection, 1 ”g/mL puromycin was added to select the stable cells.…”
Section: Cell Culture Plasmids and Lentivirus Infectionmentioning
confidence: 99%
“…We recently reported that NPC2 down-regulation is correlated with the α-fetoprotein level, tumor type, vascular invasion, and pathology stages of HCC patients. In-vitro and in vivo xenograft data demonstrated that the expression of NPC2 regulates cell proliferation, migration, and tumorigenesis by regulating ERK1/2 activation [ 21 ]. Previously, we conducted an immunohistochemical-based study to examine the expression of NPC2 in a variety of different human cancers, and meanwhile NPC2 was found to be down-regulated in human liver cirrhosis and hepatoma tissues [ 22 ].…”
Section: Introductionmentioning
confidence: 99%